2023
DOI: 10.4078/jrd.2023.0005
|View full text |Cite|
|
Sign up to set email alerts
|

Circulating leptin and its correlation with rheumatoid arthritis activity: a meta-analysis

Abstract: The aim of the study was to investigate the association between the levels of leptin in the circulating of individuals with rheumatoid arthritis (RA) and the severity of the disease. Methods: We looked through the databases of Embase, Medline, and the Cochrane Library. We conducted a meta-analysis on the correlations between circulating leptin and the Disease Activity Score 28-erythrocyte sedimentation rate (DAS28-ESR) and Creactive protein (CRP) levels in RA patients, as well as a meta-analysis of circulating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Additionally, in comparison to individual research, our study was able to provide reliable data because the findings of several independent analyses were combined, increasing the statistical power and resolution of the analysis. [28][29][30] In conclusion, our meta-analysis provides evidence that the IL-33 rs1891385 polymorphism and susceptibility to SLE, as well as blood IL-33 levels and the risk of SLE, are related. Our findings highlight the significance of genetic variables in the etiology of SLE and suggest that IL-33 is a promising biomarker for the diagnosis and monitoring of SLE.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Additionally, in comparison to individual research, our study was able to provide reliable data because the findings of several independent analyses were combined, increasing the statistical power and resolution of the analysis. [28][29][30] In conclusion, our meta-analysis provides evidence that the IL-33 rs1891385 polymorphism and susceptibility to SLE, as well as blood IL-33 levels and the risk of SLE, are related. Our findings highlight the significance of genetic variables in the etiology of SLE and suggest that IL-33 is a promising biomarker for the diagnosis and monitoring of SLE.…”
Section: Discussionmentioning
confidence: 57%
“…Additionally, in comparison to individual research, our study was able to provide reliable data because the findings of several independent analyses were combined, increasing the statistical power and resolution of the analysis. 2830…”
Section: Discussionmentioning
confidence: 99%
“…By analyzing the findings of multiple studies using a meta-analytic approach, our analysis provided a more precise assessment of the total impact size and a more accurate measurement of the relationship between genetic variation and illness. 26,27 According to our meta-analysis, there was no significant association between NLRP3 and CARD9 polymorphisms and susceptibility to RA. Although this suggests that these genetic variations have little effect on the risk of RA, it is important to recognize the limitations of our study and the complexity of RA as a disease.…”
Section: Discussionmentioning
confidence: 74%
“…2 The hormone leptin, which is produced from adipose tissue, controls metabolism and energy balance. 3,4 However, it has been postulated that it contributes to the onset and development of OA stages. [5][6][7] Previous studies have shown that patients with OA had greater levels of circulating leptin than healthy individuals, suggesting a potential association between leptin and OA.…”
Section: Introductionmentioning
confidence: 99%
“…The breakdown of cartilage in OA is thought to be caused by a combination of physical stress, inflammation, and abnormal metabolism 2 . The hormone leptin, which is produced from adipose tissue, controls metabolism and energy balance 3,4 . However, it has been postulated that it contributes to the onset and development of OA stages 5–7 .…”
Section: Introductionmentioning
confidence: 99%